Observed wave energy variations in coastal regions of the northern South China Sea during Typhoon Lupit (2021). (October 2022) - Liu, Junliang; Chen, Wuyang; Li, Junmin; Sun, Lu; Li, Bo; Shi, Ping
Abstract: Based on a two-month simultaneous in-situ wave dataset of two observational sites in the coastal regions of the northern South China Sea, the variabilities and richness of the wave energy (WE) during typhoon Lupit (2021) are studied and the discrepancies in WE responses between the two sites are also discussed. The results show that the WE of the sites mainly consists of the ocean condition whose significant wave height ranges from 0.5 to 1.5 m and energy period ranges from 5 to 8 s. It is suggested that the richness of WE could be significantly enhanced by the passage of the typhoon. For example, the energy density is enhanced by 2–4 times, i.e. from 1.2–4.2 kW/m to 5.9–9.5​ kW/m, and the available level frequency maintains as high as 100%. Moreover, the increase in WE caused by typhoons occurs several days before the passage of the typhoon and can maintain for nearly a week after its passage. Further analysis reveals that the variable intensity of the WE responses to typhoons is mainly decided by the wind speed of the typhoon and the distance between the typhoon centers to the location of the sites. Our study highlights the possibility and importance of WE to meet the basic power consumption of equipment in coastal regions, under extreme weather conditions when wind energy and solar energy are both difficult to be utilized.